1983
DOI: 10.1037/0003-066x.38.4.435
|View full text |Cite
|
Sign up to set email alerts
|

A social psychological perspective on energy conservation in residential buildings.

Abstract: The effects of videotape modeling and daily feedback on reside/ilia/ electricity conservation, home temperature, and humidity, perceived comfort, and clothing worn: Winter and summer. Unpublished manuscript,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(69 citation statements)
references
References 29 publications
0
69
0
Order By: Relevance
“…Tenants/users of technological artefacts play an important role in the configuration of the collectif energy behaviour. Several empirical studies have shown that the lifestyle and identity of tenants are equally significant factors for energy use (see, for example, Hallin et al 1986;Yates 1983;Wild & Wilhite 1985;Palmborg 1986;Skill 2008). Shove explains that energy consumption constitutes a mirror image of the collectif that individuals live in.…”
Section: Informationmentioning
confidence: 99%
“…Tenants/users of technological artefacts play an important role in the configuration of the collectif energy behaviour. Several empirical studies have shown that the lifestyle and identity of tenants are equally significant factors for energy use (see, for example, Hallin et al 1986;Yates 1983;Wild & Wilhite 1985;Palmborg 1986;Skill 2008). Shove explains that energy consumption constitutes a mirror image of the collectif that individuals live in.…”
Section: Informationmentioning
confidence: 99%
“…Prior research indicated that energy costs as a proportion of total expenditures, transaction costs of information gathering, tendency to be risk-averse, heterogeneity of preferences, lack of information, lack of trust in information sources, and adverse reactions to physical home changes explain a lack of investment in cost-effective energy efficiency home upgrades (Lutzenhiser, 1993;Frederick, Loewenstein & O'Donoghue, 2002;Wilson & Dowlatabadi, 2007). Generally, consumers tend to place a higher weight on information that is psychologically vivid and observable (Yates & Aronson, 1983). For example, households are sensitive to the initial costs of energy-efficient home upgrades and they often use current energy prices to calculate the payback for these capital investments (Gillingham, Newell & Palmer, 2009).…”
Section: Determinants Of Energy Efficiency and Conservation Behaviorsmentioning
confidence: 99%
“…Further factors on the consumer's side from empirical studies that lead to overuse of energy and reduce the effectiveness of the energy saving policies are identified (see Hausman, 1979;Kempton and Montgomery, 1982;Yates and Aronson, 1983). Such parameters are the use of higher discount rates (than the social discount rates) in consumers' energy efficiency investment decisions, salience effects whereby excessive weight is given to psychologically vivid attributes and often-incorrect use of technology.…”
Section: Consumer's Behaviormentioning
confidence: 99%